Entrepreneur's ambidexterity, knowledge brokerage and firm performance: Preliminary findings - Hashim, N.; Yap, CS Yap; Ahmad, R.; Jalaludin, F. (2017)
© 2017 IEEE. An entrepreneur's ambidexterity or ability to simultaneously and synergistically pursue both exploitation and exploration activities has been found as having positive effects on business performance. However, little is known about the antecedents and consequences of ambidexterity in entrepreneurs. This study focuses on the role of social network and environmental dynamism in affecting entrepreneur's ambidexterity. Then, to examine the importance of an ambidextrous entrepreneur, the study hypothesizes its relationship with firm performance. Data were collected from 65 entrepreneurs in the technology sector using a questionnaire survey. Conference, trade fair and exhibition, and customer are the main sources of opportunity recognition perceived by the technology entrepreneurs. The findings reveal that environmental dynamism and social network are significantly related to entrepreneur's ambidexterity, which lead to enhanced firm performance. On the other hand, knowledge brokerage activities are found to have a significant mediating effect on the relationship between ambidexterity and firm performance.